A review on advances towards achieving net-zero carbon footprint through sustainable agrivoltaic technology - George G. Njema; Nicholas Rono; Bornes C. Mosonik; Joshua K. Kibet (Bulletin of the National Research Centre)
Abstract Background The global push for decarbonization alongside the rising energy–food nexus demands has motivated substantial investments in renewable energy and agricultural infrastructure. However, the rapid expansion of large-scale solar installations has intensified competition for land use, pitting energy production against agriculture and biodiversity conservation. This conflict underscores the need for innovative solutions that balance these competing demands while promoting sustainable land use. Accordingly, this review explores the potential of agrivoltaics as a transformative strategy to address land-use conflicts. It seeks to assess the current state of agrivoltaic systems, their benefits, limitations, and future prospects, with a focus on their ability to boost land productivity while advancing renewable energy production. Main body of the abstract The study employs a comprehensive approach, including a bibliometric analysis of agrivoltaics research and an evaluation of technological innovations such as adjustable solar panels and spectral filtering techniques. These advancements aim to optimize sunlight capture and reduce shading, enhancing both energy output and crop growth. Further, the review examines case studies of successful agrivoltaic projects across diverse climates, crop types, and photovoltaic (PV) technologies, emphasizing their scalability and adaptability. The findings demonstrate that agrivoltaic systems provide significant benefits, including increased energy production and higher agricultural outputs. By creating favourable microclimates, these systems improve soil moisture retention, reduce water usage, and enhance biodiversity. Moreover, agrivoltaics contribute to climate change mitigation by lowering greenhouse gas emissions and promoting sustainable land management. Economically, they offer rural communities diversified income streams, reduced energy costs, and improved energy access in remote and peri-urban areas. Despite these advantages, challenges such as high upfront costs, regulatory barriers, and technical limitations hinder widespread adoption of this technology. Short conclusion Agrivoltaics represents a holistic approach to harmonizing energy generation and sustainable agriculture. The integration of technological innovations with environmental and economic benefits inspires the potential to transform land-use practices and support net-zero carbon footprint. However, achieving this potential requires addressing existing challenges through policy support, sensitization, and financial incentives.